Epidemiology and Economic Cost of Trypanosomosis Among SmallHolder Cattle Herders in Arba Minch and Zuria Districts, Gamo Zone, Ethiopia - Ephrem Tora; Desta Dana (SAGE Publishing, 2024)
A significant limitation to cattle production is animal trypanosomosis, which threatens household food security and livelihoods. In addition to stalling livestock productivity, the disease has a devastating impact on animal health. Besides, halting livestock productivity, the disease has a devastating effect on health. Thus, the objectives this study was to assess the epidemiology, and financial impacts of bovine trypanosomosis on livestock producers' in Arba Minch and Zuria districts of Gamo zone, Ethiopia, from December 2021 to January 2023. Both repeated survey and cross-sectional study were carried out to assess the economic losses, estimate the prevalence and assess the determinants of bovine trypanosomosis. Direct microscopy was applied using buffy coat method to detect trypanosome parasite. The study included 182 households and 384 bovine species. Bovine trypanosomosis caused substantial economic losses through cattle mortality, drug purchases, and the oxen's loss of draft power. Also, farmers spent a significantly ( P  < .05) higher amount of money treating trypanosomosis than all other diseases combined. The annual losses per household were estimated to be 9528 ± 1754 Ethiopian Birr (ETB) (95% CI: 6065-12 992) (US$ 176.4) which were spent on purchasing trypanocidal drugs per year per household. The overall mortality from bovine trypanosomiasis was 8.8%. Many farmers prioritized draft power losses as the most significant impact of the disease. Analysis of blood samples also showed a 7.8% overall prevalence of bovine trypanosomosis. The disease burden was significantly ( P  < .05) higher in the black body coat animals compared to white ones. This study showed that trypanosomosis is an important animal health problem and a potential threat to health and productivity of cattle in Arba Minch and zuria districts of Gamo, Southern Ethiopia. The common trypanocidal drugs were administered by the farmers themselves. Hence, policymakers and professionals should prevent irrational drug use and regularly monitor local trypanocide usage.